Legal Review of The Criminal Act of Ordering to Damage Cultural Heritage: A Study of Decision Number 174/PID.SUS/2022/PN SKH - Rizal Ardiansyah; Syaifuddin Zuhdi (Universitas Muhammadiyah Surakarta, 2026)
This study aims to analyze the legal considerations used by the judge in Decision Number 174/Pid. Sus/2022/PN Skh relating to a criminal act involving an order to destroy the Kartasura Baluwarti Fort Cultural Heritage, and to examine this case from an Islamic legal perspective. The method applied in this study is normative juridical, with a statutory approach and a case approach. The results of the study indicate that the panel of judges has applied Article 105 in conjunction with Article 115 paragraph (1) letter a of Law Number 11 of 2010 concerning Cultural Heritage, as well as Article 55 paragraph (1) point 1 of the Criminal Code correctly. All elements of the crime, including the element of intent and the role as the ordering party (doen pleger), has been legally proven based on the evidence presented at trial. The judge sentenced him to one year in prison plus an additional sanction in the form of an obligation to restore the fort's structure. From an Islamic legal perspective, the defendant's actions fulfill the requirements of jarimah (sharia, madi, and adabi) and are categorized as jarimah ta’zir because it damages property that has public interest (hifz al-mal). This action is also classified as fasad. This is strictly prohibited by Islamic law, as it damages non-renewable public assets and historical heritage. Both positive and Islamic law emphasize criminal liability and the importance of protecting cultural heritage as a national identity and historical legacy.